Altas habilidades/superdotação: o que dizem as pesquisas sobre estas crianças invisíveis? - Martins, Bárbara Amaral; Pedro, Ketilin Mayra; Ogeda, Clarissa Marques Maria (Associação Brasileira de Psicologia Escolar e Educacional (ABRAPEE), 2016)
Abstract This study aims to analyze Brazilian theses and dissertations, from 2005 to 2014, which deal with the identification of students with high skills / giftedness. We conducted a survey with the Bank of Theses and Dissertations of the Coordination of Personal Improvement of Higher Education, the Brazilian Library of Thesis and Dissertations, the Platform Sucupira and the main Graduate Programs with production in the area of Special Education in Brazil. The descriptors used were Identification, High Abilities, Giftedness, Precocity, Talent and Endowment. When analyzing the results we found that 20% of all publications deal with identification, with 2012 being the year with the highest number of publications. Regarding the place and type of publications, the dissertations and the Federal University of São Carlos stand out. Regarding the categorization of research, we highlight the identification of students in specific contexts, specific publics and the elaboration of identification instruments.

Resumen Este estudio tiene por objetivo analizar las tesis y tesinas brasileñas, en el período de 2005 a 2014, que abordan la temática de la identificación de estudiantes con altas habilidades/superdotación. Realizamos un levantamiento junto al Banco de Tesis y Tesinas de la Coordinación de Mejora Personal de Nivel Superior, a la Biblioteca Brasileña de Tesis y Tesinas, a la Plataforma Sucupira y a los principales Programas de Postgrado con producción en el área de la Educación Especial en Brasil. Los descriptores utilizados fueron Identificación, Altas Habilidades, Superdotación, Precocidad, Talento y Dotación. Al analizar los resultados constatamos que el 20% del total de publicaciones abordan la temática de la identificación, siendo 2012 el año con número más elevado de publicaciones. En relación al sitio y tipo de publicaciones, se destacan las tesinas y la Universidad Federal de São Carlos. Cuanto a la categorización de las investigaciones, destacamos la identificación de estudiantes en contextos específicos, públicos específicos y elaboración de instrumentos de identificación.

Resumo Este estudo tem por objetivo analisar as teses e dissertações brasileiras, no período de 2005 a 2014, que abordam a temática da identificação de estudantes com altas habilidades/superdotação. Realizamos um levantamento junto ao Banco de Teses e Dissertações da Coordenação de Aperfeiçoamento Pessoal de Nível Superior, à Biblioteca Brasileira de Teses e Dissertações, à Plataforma Sucupira e aos principais Programas de Pós-Graduação com produção na área da Educação Especial no Brasil. Os descritores utilizados foram Identificação, Altas Habilidades, Superdotação, Precocidade, Talento e Dotação. Ao analisar os resultados constatamos que 20% do total de publicações abordam a temática da identificação, sendo 2012 o ano com maior número de publicações. Em relação ao local e tipo de publicações, destacam-se as dissertações e a Universidade Federal de São Carlos. Quanto à categorização das pesquisas, destacamos a identificação de estudantes em contextos específicos, públicos específicos e elaboração de instrumentos de identificação.
High skills / giftedness: what do the research on these invisible children say?
Altas habilidades/superdotación: ¿lo qué dicen las investigaciones sobre estos niños invisibles?
Keywords: Gifted; scientific research; identification.; Superdotados; pesquisa científica; identificação.